Antifungal dipeptides incorporating an inhibitor of homoserine dehydrogenase. (11th January 2018) - Skwarecki, Andrzej S.; Schielmann, Marta; Martynow, Dorota; Kawczyński, Marcin; Wiśniewska, Aleksandra; Milewska, Maria J.; Milewski, Sławomir
Abstract : The antifungal activity of 5‐hydroxy‐4‐oxo‐l ‐norvaline (HONV), exhibited under conditions mimicking human serum, may be improved upon incorporation of this amino acid into a dipeptide structure. Several HONV‐containing dipeptides inhibited growth of human pathogenic yeasts of the Candida genus in the RPMI‐1640 medium, with minimal inhibitory concentration values in the 32 to 64 μg mL −1 range. This activity was not affected by multidrug resistance that is caused by overexpression of genes encoding drug efflux proteins. The mechanism of antifungal action of HONV dipeptides involved uptake by the oligopeptide transport system, subsequent intracellular cleavage by cytosolic peptidases, and inhibition of homoserine dehydrogenase by the released HONV. The relative transport rates determined the anticandidal activity of HONV dipeptides. Abstract : Incorporation of 5‐hydroxy‐4‐oxo‐L‐norvaline (HONV) into a dipeptide structure following the "Trojan horse" strategy afforded compounds demonstrating higher than the mother amino acid antifungal in vitro activity in the RPMI‐1640 medium. The mechanism of antifungal action of HONV‐containing dipeptides involved uptake by the oligopeptide transport system, subsequent intracellular cleavage by cytosolic peptidases and inhibition of homoserine dehydrogenase by the released HONV.